Sustainable Business Model of Shoes Garcel MSME Based on SWOT Analysis and Business Model Canvas - Ali, Mochammad Mukti (Dinasti International Journal of Education Management and Social Science, 2026)
This study is motivated by the changing dynamics of Indonesia’s creative industry, especially in the footwear fashion subsector, which is important to the economy because of MSMEs, and the growing competition in the Cibaduyut, center of Bandung City. Shoes Garcel is a micro, small, and medium enterprise that produces handmade footwear. From 2024 to 2025, Shoes Garcel experienced fluctuating sales with a declining trend. It needs to carefully review its business plan because of this. The goal of this study is to use the SWOT method along with the IFE Matrix, EFE Matrix, Space Matrix, and Business Model Canvas (BMC) to figure out the company’s strategic position and come up with a good business development model. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews with the business owner, observation of the production process, and analysis of sales and operational documents. The study’s results suggest that a company with an IFE score of 1.20 has quite significant internal qualities, especially when it comes to the quality of raw materials, design, and range of products. Meanwhile, an EFE score of -2.00 indicates that the company faces significant external pressures, particularly from cheaper substitute products and rising raw material prices. The Space Matrix mapping puts the company in Quadrant IV (Strength–Threat), which means that it should diversify depending on its fundamental strengths. When SWOT and BMC are put together, they make a business model that focuses on making high-quality handmade products stand out, boosting digital marketing, developing strategic partnerships with suppliers and e-commerce platforms, and making the supply chain work better. To sum up, Shoes Garcel long-term success doesn’t depend on how quickly it grows. Instead, it focuses on making the product more useful, transferring distribution online, and employing flexible methods to remain ahead of the competition in a crowded market.